2016
DOI: 10.4236/gsc.2016.61004
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles: A Review

Abstract: The bio-molecules from various plant components and microbial species have been used as potential agents for the synthesis of silver nanoparticles (AgNPs). In spite of a wide range of bio-molecules assisting in the process, synthesizing stable and widely applicable AgNPs by many researchers still poses a considerable challenge to the researchers. The biological agents for synthesizing AgNPs cover compounds produced naturally in microbes and plants. More than 100 different biological sources for synthesizing Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
223
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(260 citation statements)
references
References 127 publications
10
223
0
2
Order By: Relevance
“…Next, AgNPs interact with proteins containing sulfur, as well as with the compounds containing phosphorus, such as DNA. Consequently, this leads to destabilizing plasma membrane and causes protein denaturation by dissipating proton motive force, respiratory inhibition, and intracellular Adenosine triphosphate (ATP) depletion (Konop et al, ; Srikar, Giri, Pal, Mishra, & Upadhyay, ). Our experiments showed that FKDP‐AgNP possesses stronger antimicrobial properties when compared with the commercially available dressing Atrauman Ag™ (Hartmann, Poland).…”
Section: Discussionmentioning
confidence: 99%
“…Next, AgNPs interact with proteins containing sulfur, as well as with the compounds containing phosphorus, such as DNA. Consequently, this leads to destabilizing plasma membrane and causes protein denaturation by dissipating proton motive force, respiratory inhibition, and intracellular Adenosine triphosphate (ATP) depletion (Konop et al, ; Srikar, Giri, Pal, Mishra, & Upadhyay, ). Our experiments showed that FKDP‐AgNP possesses stronger antimicrobial properties when compared with the commercially available dressing Atrauman Ag™ (Hartmann, Poland).…”
Section: Discussionmentioning
confidence: 99%
“…30,31 A green chemistry route for the fabrication of SNPs would have many advantages compared with other methods, such as facile fabrication, environmentally friendly, elimination of the need for any special culture preparation and isolation method, low cost, low yields, easy scaling up for the large-scale fabrication of nanoparticles, and not consuming a lot of energy. 1,3134 …”
Section: Introductionmentioning
confidence: 99%
“…The nanoparticles synthesized using green technology are found to be effective than those produced by chemical methods [7]. In this research work, the synthesis of AgNPs using the extract of the seeds of A. graveolens was studied.…”
Section: Resultsmentioning
confidence: 99%